2014
DOI: 10.3389/fnhum.2014.00517
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of reasoning by analogy in schizophrenia and autism spectrum disorder

Abstract: Relational reasoning ability relies upon by both cognitive and social factors. We compared analogical reasoning performance in healthy controls (HC) to performance in individuals with Autism Spectrum Disorder (ASD), and individuals with schizophrenia (SZ). The experimental task required participants to find correspondences between drawings of scenes. Participants were asked to infer which item within one scene best matched a relational item within the second scene. We varied relational complexity, presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 70 publications
0
27
0
1
Order By: Relevance
“…Children with SLI exhibit poorer deductive reasoning (Newton et al, 2010 ) and analogical reasoning (Leroy et al, 2012 , 2014 ) than normally developing children. Individuals with autism spectrum disorder (ASD) exhibit deficits in analogical reasoning particularly about non-living items (Krawczyk et al, 2014 ) and defeasible conditional reasoning (Pijnacker et al, 2009 ). Adolescents with moderate to severe traumatic brain injury exhibit impairments in analogical reasoning ability (Krawczyk et al, 2010 ).…”
Section: Empirical Support From Pragmatic Disordersmentioning
confidence: 99%
“…Children with SLI exhibit poorer deductive reasoning (Newton et al, 2010 ) and analogical reasoning (Leroy et al, 2012 , 2014 ) than normally developing children. Individuals with autism spectrum disorder (ASD) exhibit deficits in analogical reasoning particularly about non-living items (Krawczyk et al, 2014 ) and defeasible conditional reasoning (Pijnacker et al, 2009 ). Adolescents with moderate to severe traumatic brain injury exhibit impairments in analogical reasoning ability (Krawczyk et al, 2010 ).…”
Section: Empirical Support From Pragmatic Disordersmentioning
confidence: 99%
“…In an earlier study, Reed (1996) reported that children with ASD performed at lower levels on analogical reasoning tests than did IQ-matched typically developing (TD) children and children with intellectual disabilities. In contrast, other studies have found comparable performance between ASD and control groups when IQ scores were matched ( Scott and Baron-Cohen, 1996 ; Sahyoun et al, 2009 ; Morsanyi and Holyoak, 2010 ) and when IQ scores were not matched ( Green et al, 2014 ; Krawczyk et al, 2014 ). These inconsistent findings may be attributable to differences in study paradigms and participant characteristics.…”
Section: Introductionmentioning
confidence: 75%
“…This work extends previous research that has primarily focused on nonsocial analogical reasoning in ASD (Morsanyi and Holyoak, 2010; Scott and Baron-Cohen, 1996; Green et al, 2014), and begins to characterize the developmental trajectory of social analogical reasoning, albeit cross-sectionally. The use of photographic stimuli depicting real people engaging in social interactions is also a step toward more ecologically valid information processing relative to line drawings and cartoon images that have generally been used in studies of analogical reasoning in ASD and typically-developing children (Krawczyk et al, 2014; Morsanyi and Holyoak, 2010; Scott and Baron-Cohen, 1996). Though this study is not ecologically valid as a measure of cognition in real-world social situations, improving the ecological validity of information processing in laboratory tasks as much as possible is nonetheless helpful for better understanding of social analogical reasoning and social cognition more generally.…”
Section: Discussionmentioning
confidence: 99%